The Routledge history of happiness
1 online resource.
Keywords: "Unmatched in originality, breadth, and scope, The Routledge History of Happiness features chapters that explore the history, anthropology, and psychology of happiness across the globe. The Routledge History of Happiness is of great use to all undergraduates, postgraduates, and scholars interested in the global history of emotions"--